2017
DOI: 10.5195/jmla.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

Unanswered clinical questions: a survey of specialists and primary care providers

Abstract: ObjectiveWith the myriad of cases presented to clinicians every day at our integrated academic health system, clinical questions are bound to arise. Clinicians need to recognize these knowledge gaps and act on them. However, for many reasons, clinicians might not seek answers to these questions. Our goal was to investigate the rationale and process behind these unanswered clinical questions. Subsequently, we explored the use of biomedical information resources among specialists and primary care providers and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 12 publications
3
24
0
1
Order By: Relevance
“…The ability to use information-seeking behavior with specific clinical questions, methods, and reliable websites are important to clinicians [ 1 , 2 ]. A survey of clinicians by White et al [ 3 ] found that only 65% used PubMed often.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to use information-seeking behavior with specific clinical questions, methods, and reliable websites are important to clinicians [ 1 , 2 ]. A survey of clinicians by White et al [ 3 ] found that only 65% used PubMed often.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent survey among clinicians shows that 79% of participants used mobile devices to access clinical information and 72% of participants used clinical applications on their devices [ 2 ]. There is substantial evidence of the effectiveness of mobile devices that support decision making in the clinical practice of physicians and educational training programs for medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread clinician awareness of the existence of high-quality primary research such as randomised controlled trials and research syntheses in the form of systematic reviews and clinical practice guidelines is an important factor in shortening the time lag between research production and its implementation into routine clinical practice (Fischer, Lange, Klose, Greiner, & Kraemer, 2016). Timelier identification of welldesigned, clinically relevant research evidence is also likely to minimise resource wastage and reduce the possibility of patients being administered ineffective, or even harmful, therapies (Brassil, Gunn, Shenoy, & Blanchard, 2017;Dunn, Marshall, Wells, & Backus, 2017;Klein, Ross, Adams, & Gilbert, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies have shown that clinicians do not pursue or find answers for about half of their clinical questions that arise during everyday practice [ 5 8 ]. The greatest barrier to answering clinical questions, insufficient time, has also contributed to physician burnout and poor patient outcomes [ 9 , 10 ]. Indeed, time pressure may detract from physicians’ satisfaction and can stress their relationships with patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, some CLs act as embedded librarians, saving physicians time by performing literature searches and assisting in answering clinical questions that arise while rounding during real-time patient care [ 15 , 22 , 23 ]. A recent study suggests that deploying CLs into clinical settings in this manner could encourage physicians to answer clinical questions, become lifelong learners, and ensure patient safety [ 9 ].…”
Section: Introductionmentioning
confidence: 99%